2009
DOI: 10.1080/17513750802376313
|View full text |Cite
|
Sign up to set email alerts
|

Species decline and extinction: synergy of infectious disease and Allee effect?

Abstract: Host-parasite models with density-dependent (mass action) incidence and a critical Allee effect in host growth can explain both species decline and disappearance (extinction). The behaviour of the model is consistent with both the novel pathogen hypothesis and the endemic pathogen hypothesis for chytridiomycosis. Mathematically, the transition from decline to disappearance is mediated by a Hopf bifurcation and is marked by the occurrence of a heteroclinic orbit. The Hopf bifurcation is supercritical if intra-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…In a recent paper, Hilker et al [14] showed that in the presence of strong Allee effect in host demographics, a simple susceptible-infected (SI) epidemic model can exhibit stable periodic orbits (by Hopf bifurcation), multiple stationary states, and catastrophic collapses of endemic equilibria. Using a similar SI model with the strong Allee effect, Thieme et al [16] established by mathematical theorems that the transition from population decline to population collapse is mediated by a Hopf bifurcation and a heteroclinic orbit. The SI models of Hilker et al and Thieme et al are structurally similar to predator-prey models that have an Allee effect in the prey population and a linear functional response (prey eaten per predator per unit time) [2,3,6,10,[12][13][14]17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper, Hilker et al [14] showed that in the presence of strong Allee effect in host demographics, a simple susceptible-infected (SI) epidemic model can exhibit stable periodic orbits (by Hopf bifurcation), multiple stationary states, and catastrophic collapses of endemic equilibria. Using a similar SI model with the strong Allee effect, Thieme et al [16] established by mathematical theorems that the transition from population decline to population collapse is mediated by a Hopf bifurcation and a heteroclinic orbit. The SI models of Hilker et al and Thieme et al are structurally similar to predator-prey models that have an Allee effect in the prey population and a linear functional response (prey eaten per predator per unit time) [2,3,6,10,[12][13][14]17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In density-dependent transmission models, abrupt host extinction seems to be less general. In [57] multiple equilibria are not possible -this may be due to the assumptions that infectives do not reproduce at all or that mortality is density-independent. The model in [36] -the same as in Equations (1) and (2) but with density-dependent incidence -allows for fold catastrophes, but in a more restricted parameter range (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Numerical experiments show that the frequency-dependent model by Deredec and Courchamp [15] exhibits a saddle-node bifurcation as well (the authors did not report the possibility of multiple endemic equilibria). Furthermore, if one changes the density-dependent model by Thieme et al [57] to obey a frequency-dependent incidence, two endemic equilibria and their disappearance in a saddle-node bifurcation too become possible.…”
Section: Discussionmentioning
confidence: 99%
“…It receives considerable attention recently in mathematiEmail addresses: kunyasco@yahoo.com (Salisu Usaini * ), roumen.anguelov@up.ac.za (Roumen Anguelov), salisu.garba@up.ac.za (Salisu M Garba)cal models of ecology and epidemiology (for the recent works see (David et al, 2007;Friedman and Yakubu, 2012b;Hilker et al, 2007;Ling-ling and Cang, 2009;Kang and Castillo-Chavez, 2014;Sophia and Jang, 2011;Thieme et al, 2009) and the references therein). The Allee effect is a phenomenon in biology characterized by a positive relationship between population density or size and the per capita population growth rate in small populations .…”
Section: Introductionmentioning
confidence: 99%